'Exploring, progressing and harvesting'. Participant experiences of engaging in speech-language pathology research within a cross-cultural setting. (1st October 2020) - Atherton, Marie; Lê Khánh, Điền; Quyên, Hoàng Văn; Thảo, Huỳnh Bích; Thanh, Lê Thị; Cường, Lê Văn; Loan, Lưu Thị Thanh; Hiền, Trương Thị Minh; Davidson, Bronwyn; McAllister, Lindy
ABSTRACT: Objective: This qualitative descriptive study explored the experiences of a group of Vietnamese speech-language pathologists who collaborated in a longitudinal research programme with an Australian researcher. Conducted between 2013 and 2016, the research programme sought to document the development of the speech-language pathology profession in Vietnam through the experiences of Vietnam's first university-trained speech-language pathologists. Method: Utilising a series of questions, seven participants explored their experiences of engaging in the research, and the advice they would offer others who were considering involvement in cross-cultural research. Qualitative content analysis was used to analyse the data. Result: Four main categories of experience were identified: capacity building, team work and group processes, cross-cultural issues, and advice for others. Uncertainty as to the collaborative ethos of the research design informed recommendations for future researchers and participants. The relationship between the researcher, interpreter and participants was considered critical to successful engagement in cross-cultural research. Conclusion: This research illuminated the perspectives of the research participants and highlighted a complex interplay of factors informing and shaping participation in cross-cultural research. Researchers engaging in research within contexts that are not their own must consider how the research can proceed in a culturally safe manner and support findings that are responsive to and reflective of local context.